Violence Against Native Women - Bubar, Roe (Social justice, 2004)
Part of a special issue on native women and state violence. The writers explore issues pertinent to understanding the current high rates of violent victimization of native women in North America. They investigate the historical experience of colonization and violence as well as the contemporary tribal community context and identify factors that contribute to the high levels of abuse to which indigenous women are subjected. They report on a roundtable discussion with tribal women on violence against women; discuss implications for research and practice; and present a community readiness model as a potential tool for addressing the issue.